Broken Gears: The Value Added of Higher Education on Teachers' Academic Achievement - Carlos Felipe Balcázar; Hugo Nopo (Institute for the Study of Labor (IZA), 2014)
A growing literature establishes that good teachers are essential for high quality educational systems. However, little is known about teachers' skills formation during their college years. In this paper we use a novel panel data set combining two standardized tests for Colombian students: one that is taken at the end of senior year in high school and the other when students are near graduation from college. Accounting for selection into majors we test for the extent to which education majors relatively improve or deteriorate their skills in comparison to students in other programs. We analyze three sets of skills: quantitative reasoning, native language (Spanish) and foreign language (English). After around 5 years of college, teachers' skills vis-à-vis those in other majors deteriorate in quantitative reasoning, although they deteriorate less for those in math-oriented programs. For native and foreign language we do not find evidence of robust changes in relative learning.
Keywords: I2; I21; J24; 330; teacher performance; career choice; self-selection; relative learning mobility